2010
DOI: 10.5860/rbm.11.2.337
|View full text |Cite
|
Sign up to set email alerts
|

Bringing Rare Books to Light: The State of the Profession

Abstract: When the AssociAtion of ReseARch LibRARies (ARL) released the results of its 1998 survey of special collections, the backlog of unprocessed and uncataloged collections emerged as one of the most serious and daunting issues facing the profession. An increasingly enthusiastic professional discourse about the "hidden collections" problem, as it became known, has developed as a result. The ARL Special Collections Task Force, convened in 2001 and dissolved in 2006, focused on exposing hidden collections as a top ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Similar research was conducted in the UK, leading to the publication of RLUK's 2010 Major new survey of RetroCon and a joint RLUK/London Library Hidden Collections report (RLUK, 2012). Scholarly research and discussion of these hidden collections findings include Mandel (2004), Tabb (2004), Katz (2004), Yakel (2005), Prochaska (2008), Dooley (2009), and Hubbard and Myers (2010).…”
Section: The Extent Of the Hidden Collections Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar research was conducted in the UK, leading to the publication of RLUK's 2010 Major new survey of RetroCon and a joint RLUK/London Library Hidden Collections report (RLUK, 2012). Scholarly research and discussion of these hidden collections findings include Mandel (2004), Tabb (2004), Katz (2004), Yakel (2005), Prochaska (2008), Dooley (2009), and Hubbard and Myers (2010).…”
Section: The Extent Of the Hidden Collections Problemmentioning
confidence: 99%
“…Indeed, implementing "digitization without metadata is an abrogation of stewardship" (ARL, 2009, p. 22) which would only create further hidden and inaccessible material: "discovery, that primary function of research in Special Collections, is not possible without description and guidance" (Goldman, 2011, p. 23). Furthermore, Hubbard and Myers' (2010) survey reveals a strong sense among American librarians that, despite institutional backlogs and hidden collections, "changes in cataloging practice would create unacceptable compromises due to the unique descriptive needs of rare books" (p. 143). Ultimately, therefore, though local decisions must be made regarding the level of cataloging detail deemed appropriate, adherence to national standards and practices should still be maintained (Jones, 2003).…”
Section: Proposed Solutions To Hidden Collectionsmentioning
confidence: 99%
“…13 Hubbard and Myers' 2010 survey of rare books catalogers found that 97.8 percent of the respondents still reported a backlog at their institutions, and although Dooley and Luce's report of that same year found backlogs for some types of materials had decreased at more than half of the institutions surveyed, the size of the collections continues to grow. 14 While this situation presents challenges for library staff, the real harm is to users. Under-cataloged collections result in inadequate intellectual access to those resources, particularly hindering the research efforts of some of libraries' most vulnerable users who lack the financial means to travel to other institutions, such as undergraduates, graduate students, and junior faculty.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In America the paper ‘Hidden collections’, the results of which were summarised by Beth M. Russell (2004), looked at the backlog in cataloguing special collections, including modern special collections. This led to the examination of processes to see how they could be streamlined, and to observations on the benefit of a high quantity of adequate catalogue records over a small number of very detailed ones (Hubbard and Myers, 2010: 137, 142). In Britain, a ‘Survey of Outstanding Material for Retrospective Conversion and Retrospective Cataloguing in CURL Libraries’, conducted by the Consortium of University and Research Libraries (CURL) in 2004, revealed large cataloguing backlogs here too confirmed by a further study in 2010 (Garcia-Ontiveros, 2010).…”
Section: Introductionmentioning
confidence: 99%